ANALISIS HUKUM TERHADAP FAKTOR-FAKTOR YANG MELATARBELAKANGI TERJADINYA NIKAH SIRRI DAN DAMPAKNYA TERHADAP PEREMPUAN (ISTRI) DAN ANAK-ANAK - Siti Ummu Adillah (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Sirri marriage reality is like an iceberg phenomenon, many occur in society, but the tappears only small surface and publicized when the perpetrator of public officials or public figures.The negative impact of sirri marriage experienced by many women (wives) and children if her husband is not responsible.The factors underlying the community do sirri marriage is due to economic factors, factors not old enough, factor bond department/work or school, it was thought that the marriage valid according the religion, recording the only orderly administration, pregnant outside of marriage due to promiscuity, lack of understanding and awareness of marriage records, social factors, the difficulty of the rule of polygamy and the persistence of people who do sirri marriage because no one wants to take firm action against perpetrators of irresponsible. While positive and negative impact on women sirri marriage (wife) and children legally is actually having an impact for husbands, wives and children, both in terms of positive or negative side, its just not comparable to the positive side of negative impact and judging from the many cases, the negative side more experienced women (wives) and children than those experienced by husbands. Keywords: sirri marriage, impact, woman (wife), children